(untitled) (Journal of history, 2021)
Clothing, reflecting the centuries-old history of the people, has a special place in its material culture. It reflects the aesthetic ideals of the people, their way of life, and social equivalents. Changing under the influence of new economic and political conditions of life, the clothing of nomads steadfastly retains a number of ancient features in forms, details of cut and jewelry, the identification of which is material for studying the specific history of the ancient Kazakh people and its culture. The article considers traditional Kazakh clothing from the collection of the Central State Museum of the Republic of Kazakhstan as one of the basic components of the subsistence (life support) system of the ethnic group. The issues of the composition, history of formation and geography of acquisition of the collections of traditional Kazakh clothes of the ethnographic fund of the Central State Museum (CSM RK) are considered, since the problem of constant replenishment of the funds of ethnographic collections in domestic museums is an urgent scientific and scientific-practical problem The authors developed a typology of clothing in accordance with seasonal, age and gender, anthromorphic principles, and socio-symbolic and regional features. Based on the materials of the above museum, the authors revealed that the work of replenishing the funds is carried out on the basis of donation and acquisition by ethnographic expeditions and persons organized to study special topics, and that the geography of their acquisition is formed from almost all regions of Kazakhstan and neighboring countries. Key words: Central State museum of the Republic of Kazakhstan, collection of traditional clothing, subsistence system, composition of clothing, geography of accumulation, typology